Handgrip strength is independently associated with physical quality of life in patients undergoing maintenance hemodialysis: a cross-sectional study - Li, Chunlei; Pan, Xiangyou; Xu, Shilin; Hu, Jianguang; Zhong, Xiaoshi; Wen, Luona; Qiu, Jingxian; Tan, Rongshao (Frontiers in Nutrition, 2024)
Objective: We aimed to identify the association between Health-related quality of life (HRQoL) and muscle strength in patients undergoing maintenance hemodialysis (MHD).In this cross-sectional study from March 2021 to December 2021, 110 MHD patients with a mean age of 63.9 ± 13.0 years and a median dialysis vintage of 25.5 (12.0-52.3) months, were enrolled at a hemodialysis center in Guangzhou city, China.HRQoL was assessed using the Short Form 36 Health Survey (SF-36) and converted into the Physical Component Summary (PCS) and the Mental Component Summary (MCS). The groups were assigned according to the mean score of PCS and MCS, and those with higher PCS/MCS scores (high-PCS/MCS) were compared with those with lower PCS/MCS scores (low-PCS/MCS). Independent factors were evaluated using multivariate analysis. Muscle strength was estimated by handgrip strength (HGS).The mean HGS was 23.7 ± 9.60 kg in men and 14.3 ± 5.30 kg in women. Compared to the high-PCS group, the low-PCS group had older age, higher levels of creatinine, total cholesterol, high-sensitivity C-reactive protein (hsCRP) and interleukin-6 (IL-6), and had lower HGS (all p <0.05). After adjusting for confounding factors in different models, the five-model multivariate binary logistic regression analyses revealed that HGS was the only independent factor in PCS domain, but not in MCS.Conclusions: HGS may be an independent factor of poor HRQoL in MHD patients, particularly in relation to physical health. The management of muscle strength may improve the HRQoL in MHD patients.